Molecular Survey of Dirofilaria and Leishmania Species in Dogs from Central Balkan - Tasić-Otašević, Suzana; Savić, Sara; Jurhar Pavlova, Maja; Stefanovska, Jovana; Stalević, Marko; Ignjatović, Aleksandra; Ranđelović, Marina; Gajić, Bojan; Cvetkovikj, Aleksandar; Gabrielli, Simona (MDPI AG, 2022)
Dirofilariosis and leishmaniosis are severe parasitic diseases in dogs, and their causative agents can also be pathogenic to humans. In this study, we conducted a multicentric survey in the regions of Serbia and North Macedonia with the goal to establish an epidemiological scenario of dirofilariosis and leishmaniosis in the territory of Central Balkan. Using molecular analyses, a total of 535 dogs from Northern Serbia (NS), Southern Serbia (SS) and North Macedonia (NM) were screened for the presence of Dirofilaria spp. and Leishmania spp. We confirmed that Central Balkan is an endemic region for Dirofilaria (D.) immitis, as it was found to be the dominant species in this area, with the highest prevalence of 8.75% in NM, followed by NS (6.68%) and a significantly lower prevalence in SS (1.51%). Two dogs (2.5%) from NM were positive for Leishmania (L.) infantum infection. None of the dogs from Serbia tested positive for Leishmania spp. High prevalence and dominance of D. immitis species, and the rising threat of L. infantum spread to the territory of Serbia, suggest that preventive measures are of a great necessity to combat the spread of these vector-borne zoonoses.